Insole composite material with bacteriostasis and deodorization functions

By adding functional additives and wear-resistant modified components to the insole composite material, and connecting coffee grounds with L-arginine by covalent grafting method, the shortcomings of the existing EVA insoles in antibacterial and deodorizing and wear-resistant properties are solved, and the good antibacterial and deodorizing and wear-resistant effects of the insoles are achieved, and the service life is extended.

CN119735887AActive Publication Date: 2025-04-01DONGGUAN YUANCHUANG DIGITAL TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411928236.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing EVA insoles have shortcomings in antibacterial and deodorizing and wear resistance, resulting in foot odor problems and short service life.

Method used

By adding functional additives and wear-resistant modified components to the preparation process of the insole composite material, the coffee grounds and L-arginine are chemically linked by covalent grafting method to prepare insole composite material with antibacterial and deodorizing properties and wear-resistant properties.

Benefits of technology

It achieves good antibacterial and deodorizing properties and wear resistance of insole composite materials, extends the service life of insoles and reduces the generation of odors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735887A_ABST
    Figure CN119735887A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses an insole composite material with bacteriostasis and deodorization functions, the insole composite material comprises the following raw materials: EVA, POE elastomer, talcum powder, a functional additive, a wear-resistant modified component, stearic acid, a cross-linking agent and a foaming agent; wherein the functional additive is used for chemically connecting coffee grounds with L-arginine in a covalent grafting manner, so that the prepared insole composite material has good antibacterial and deodorizing performance, and the generation of peculiar smell is reduced; the wear-resistant modified component generates a special ball effect in the matrix, so that the wear resistance of the insole composite material is improved, the wear of the insole in daily use is reduced, the service life of the insole composite material is prolonged, and the insole composite material has higher actual popularization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a shoe insole composite material with antibacterial and deodorizing functions. Background Art

[0002] As an indispensable part of footwear, insoles not only improve the wearing comfort, but also play an important role in foot health. There are various types of insoles on the market. Insoles are classified by material into EVA insoles, sponge insoles, silicone insoles, TPR insoles, cloth insoles, etc. Among them, EVA insoles have become one of the preferred materials in insole production due to their good cushioning performance, high comfort and easy processing.

[0003] In recent years, with the improvement of people's quality of life and the enhancement of health awareness, the hygienic performance of insoles has become the focus of consumers' attention. However, ordinary EVA insoles often have shortcomings in antibacterial and deodorization. Since the sweat glands of the feet are relatively dense and easily secrete a large amount of sweat, the feet are prone to breed bacteria, fungi and other microorganisms in a humid environment. Bacteria decompose organic matter in sweat and produce substances with special odors, which cause foot odor. This not only affects consumers' wearing experience, but also poses a threat to their health. In addition, the wear resistance of ordinary EVA insoles is poor. Insoles will be subject to friction and wear during daily use, so they need to have good wear resistance to extend their service life.

[0004] In the prior art, the improvement of insole performance is often achieved by optimizing the basic formula. For example, the invention patent with the announcement number CN116218071B discloses an EVA antibacterial insole and its preparation method. The invention adds antibacterial agents, bioactive glass and nano-copper, to the basic formula, so that the insole itself has an antibacterial effect, avoiding the risk of the antibacterial layer of the traditional antibacterial insole falling off, and enhancing the stability and sustainability of the antibacterial effect; and through the limitation of a special range and ratio, the synergistic effect of bioactive glass and nano-copper is optimized, which has the advantages of high antibacterial rate and stable and lasting antibacterial effect. Therefore, a high-performance insole composite material can be prepared by adding optimized components in a targeted manner during the preparation of the insole composite material. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a composite insole material with antibacterial and deodorizing functions.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A composite shoe insole material with antibacterial and deodorizing functions comprises the following raw materials in parts by weight: 40 to 60 parts of EVA, 20 to 30 parts of POE elastomer, 5 to 15 parts of talcum powder, 4 to 6 parts of functional additives, 3 to 7 parts of wear-resistant modified components, 0.5 to 0.9 parts of stearic acid, 0.4 to 0.6 parts of cross-linking agent, and 2 to 3 parts of foaming agent.

[0008] Furthermore, the preparation method of the functional additive comprises the following steps:

[0009] S1: drying the coffee grounds at 70-90°C for 4-8h, placing them in a glass fiber sleeve, and then placing them in an extraction tube, adding a solvent in a flask, and controlling the temperature at 80-90°C, performing 4-6 reflux operations, each reflux time being 8-12min, and then drying the deoiled coffee grounds to obtain pretreated coffee grounds;

[0010] S2: under nitrogen protection, the pretreated coffee grounds are added to N,N-dimethylformamide, ultrasonically dispersed for 20 to 30 minutes, and then isocyanoethyl methacrylate and tin catalyst are added. After the addition is completed, the temperature is raised to 70 to 80°C, and the mixture is stirred for 5 to 7 hours at this temperature, and then allowed to stand for precipitation. The solid material is collected, washed, and vacuum dried to obtain the modified coffee grounds;

[0011] S3: Mix the modified coffee grounds with deionized water, pour into a reactor, start stirring until a uniform dispersion is formed, add L-arginine, stir at a temperature of 25 to 30° C. for 6 to 8 hours, separate the product, and obtain the functional additive; in step S2, the tin catalyst is any one of dibutyltin didodecylsulfide, stannous octoate or dibutyltin dilaurate.

[0012] Furthermore, in step S3, the mass ratio of the modified coffee grounds to L-arginine is 1:0.1-0.3.

[0013] It can be inferred that the principle of the above scheme is: in step S1, the coffee grounds are deoiled by Soxhlet extraction to obtain pretreated coffee grounds; in step S2, the coffee grounds are deoiled to expose the hydroxyl groups thereon, which can react with the isocyanate groups in the structure of isocyanoethyl methacrylate under the action of an organic tin catalyst, thereby introducing alkenyl groups into the surface of the coffee grounds to obtain modified coffee grounds; in step S3, the alkenyl groups on the surface of the modified coffee grounds can undergo Michael addition reaction with the amino groups in the structure of L-arginine to obtain functional additives.

[0014] Furthermore, the preparation method of the wear-resistant modified component comprises the following steps:

[0015] SS1: Mullite fiber is mixed with deionized water, ultrasonically treated for 30 to 50 minutes, then dopamine is added, the pH value of the system is adjusted with Tris-HCl buffer, stirred at room temperature for 12 to 36 hours, allowed to stand and precipitate, solid materials are collected, washed, and vacuum dried to obtain modified mullite fiber;

[0016] SS2: Ultrasonic disperse 4g of modified mullite fiber in deionized water, add 3g of aluminum nitrate, stir at room temperature for 35-45min, then add ammonia water, stir for 30-50min, filter, wash and dry to obtain the wear-resistant modified component.

[0017] Furthermore, in step SS1, the pH value of the system is 8-9.

[0018] Furthermore, in step SS2, the mass fraction of the ammonia water is 10% to 60%.

[0019] It can be inferred that the principle of the above scheme is: in step SS1, dopamine can undergo an oxidative self-polymerization reaction on the surface of the mullite fiber under alkaline aerobic conditions, thereby coating the surface of the mullite fiber with a polydopamine layer to obtain a modified mullite fiber; in step SS2, the -N= group on the surface of the modified mullite fiber can react with Al 3+ Generate coordination bonds and convert Al 3+ Fixed to the surface of mullite fiber, and then use acid-base neutralization to make Al 3+ Aluminum hydroxide precipitate is generated, so that the surface of the mullite fiber is loaded with aluminum hydroxide, i.e., the wear-resistant modification component.

[0020] Furthermore, the preparation method of the insole composite material comprises the following steps:

[0021] (1) raising the temperature of the internal mixer to 100-110° C., adding EVA and POE elastomers, and opening the internal mixer for internal mixing. When the temperature rises to 110-120° C., adding talcum powder, functional additives, wear-resistant modification components and stearic acid. When the temperature rises to 120-130° C., adding a crosslinking agent and a foaming agent, mixing for 3-6 minutes, and obtaining a mixed material.

[0022] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 80-90° C., the roller gap to 2-6 mm, and controlling the temperature of the final sheet after the mixed material is uniform to 40-70° C., and the sheet thickness to 4-7 mm, to obtain the material after the mixing;

[0023] (3) placing the material after the open mixing in a foaming mold for foaming, and naturally cooling the semi-finished product after foaming for 40 to 50 hours to obtain a foamed sheet;

[0024] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0025] Furthermore, in step (1), the cross-linking agent is any one of 1,4-di-tert-butyl peroxide isopropylbenzene or diisopropylbenzene peroxide; and the foaming agent is any one of azodicarbonamide, sodium bicarbonate, ammonium bicarbonate or expandable microspheres.

[0026] Furthermore, in step (3), during the foaming treatment, the foaming temperature is set to 160-170° C., the foaming pressure is set to 10-15 MPa, and the foaming time is set to 10-15 min.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention adds functional additives and wear-resistant modified components during the preparation of the insole composite material. The raw materials cooperate with each other, so that the prepared insole composite material has good antibacterial and deodorizing properties and wear resistance, which is beneficial to extending the service life of the insole product and has greater practical promotion value.

[0029] (2) The present invention chemically links coffee grounds and L-arginine by covalent grafting to prepare a functional additive. On the one hand, the coffee grounds in the functional additive have both hygroscopic and deodorizing effects, so that the prepared insole composite material has good deodorizing performance. On the other hand, the strongly positively charged guanidine group in the functional additive can adsorb and bind to various negatively charged microorganisms such as bacteria and viruses, so that the insole composite material exhibits a good antibacterial effect, thereby reducing the generation of odor.

[0030] (3) The present invention adds a wear-resistant modified component as a functional filler into the matrix. After the mullite fiber is coated with polydopamine, the interfacial affinity between the wear-resistant modified component and the matrix is ​​effectively improved, and the wear-resistant modified component can be relatively evenly dispersed in the matrix to form a good filling effect, and can produce a special ball effect, thereby improving the wear resistance of the insole composite material, reducing the wear of the insole in daily use, and effectively extending the service life of the insole.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 This is an infrared spectrum test chart of the functional additive prepared in Example 1 of the present invention.

[0034] Figure 2 This is an infrared spectrum test chart of the modified mullite fiber prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] 1. Preparation of functional additives

[0038] S1: 5 g of coffee grounds were dried at 80°C for 6 h, then placed in a glass fiber sleeve and then placed in an extraction tube, 35 ml of n-hexane was added to the flask, and the temperature was controlled at 85°C, and refluxed for 5 times, each reflux time was 10 min, and then the de-oiled coffee grounds were dried to obtain pretreated coffee grounds;

[0039] S2: Under nitrogen protection, 6 g of pretreated coffee grounds were added to N,N-dimethylformamide, and ultrasonically dispersed for 25 min. Then, 1.2 g of isocyanoethyl methacrylate and 0.05 g of stannous octoate were added. After the addition, the temperature was raised to 75°C, and the mixture was stirred for 6 h. The mixture was allowed to stand and precipitate. The solid material was collected, washed, and vacuum dried to obtain modified coffee grounds.

[0040] S3: Mix 5 g of modified coffee grounds with deionized water, pour into a reactor, start stirring until a uniform dispersion is formed, add 1.4 g of L-arginine, stir at 28°C for 7 hours, separate the product, and obtain the functional additive.

[0041] The functional additives were analyzed by infrared spectroscopy using a TENSOR 27 Fourier transform infrared spectrometer produced by BRUKER, Germany. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of functional additives, 1680cm -1 The absorption peak of C=O in the carbamate structure appears at 1760 cm -1 The absorption peak of the ester group C=O appears at 1654 cm -1 The absorption peak of guanidine C=N appears at 1740 cm -1The absorption peak of the carboxyl group C=O appears at 3390 cm -1 The absorption peak of -NH appears at

[0042] 2. Preparation of wear-resistant modified components

[0043] SS1: 5 g of mullite fiber was mixed with deionized water, ultrasonically treated for 40 min, then 1.5 g of dopamine was added, the pH value of the system was adjusted to 8.5 with Tris-HCl buffer, stirred at room temperature for 24 h, allowed to stand for precipitation, solid materials were collected, washed, and vacuum dried to obtain modified mullite fiber;

[0044] The modified mullite fiber was analyzed by infrared spectroscopy using a TENSOR 27 Fourier transform infrared spectrometer produced by BRUKER, Germany. Figure 2 As shown in the infrared spectrum of modified mullite fiber, 3075cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appears at 3390 cm -1 The absorption peak of NH appears at 1236cm -1 The absorption peak of CN appears at 3291cm -1 The absorption peak of hydroxyl group OH appears at

[0045] SS2: Ultrasonic disperse 4 g of modified mullite fiber in deionized water, add 3 g of aluminum nitrate, stir at room temperature for 40 min, then add 1 g of 40% ammonia water, stir for 40 min, filter, wash and dry to obtain the wear-resistant modified component.

[0046] 3. Preparation of insole composite materials

[0047] (1) The temperature of the internal mixer was raised to 100° C., 40 g of EVA and 20 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 110° C., 5 g of talc, 4 g of functional additives, 3 g of wear-resistant modification components and 0.5 g of stearic acid were added. When the temperature was raised to 120° C., 0.4 g of diisopropylbenzene peroxide and 2 g of azodicarbonamide were added, and the mixture was mixed for 3 min to obtain a mixed material.

[0048] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 80° C. and the roller gap to 2 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 60° C. and the sheet thickness is 4 mm, thereby obtaining the material after the mixing;

[0049] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 160° C., the foaming pressure to 10 MPa, the foaming time to 10 min, and naturally cooling the semi-finished product after foaming for 40 h to obtain a foamed sheet;

[0050] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0051] Example 2

[0052] Preparation of insole composite materials

[0053] (1) The temperature of the internal mixer was raised to 105° C., 50 g of EVA and 25 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 115° C., 10 g of talc, 5.5 g of functional additives, 6 g of wear-resistant modification components and 0.7 g of stearic acid were added. When the temperature was raised to 125° C., 0.5 g of diisopropylbenzene peroxide and 2.5 g of azodicarbonamide were added, and the mixture was mixed for 5 min to obtain a mixed material.

[0054] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 85° C. and the roller gap to 4 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 70° C. and the sheet thickness is 5 mm, thereby obtaining the material after the mixing;

[0055] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 165° C., the foaming pressure to 12 MPa, the foaming time to 12 min, and naturally cooling the semi-finished product after foaming for 45 h to obtain a foamed sheet;

[0056] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0057] The preparation method of the functional additive and the wear-resistant modified component is the same as that in Example 1.

[0058] Example 3

[0059] Preparation of insole composite materials

[0060] (1) The temperature of the internal mixer was raised to 110° C., 60 g of EVA and 30 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 120° C., 15 g of talc, 6 g of functional additives, 7 g of wear-resistant modification components and 0.9 g of stearic acid were added. When the temperature was raised to 130° C., 0.6 g of diisopropylbenzene peroxide and 3 g of azodicarbonamide were added, and the mixture was mixed for 6 min to obtain a mixed material.

[0061] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 90° C. and the roller gap to 6 mm. After the mixed materials are evenly mixed, the temperature of the final sheet is controlled at 80° C. and the sheet thickness is 7 mm, thereby obtaining the material after the mixing;

[0062] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 170° C., the foaming pressure to 15 MPa, the foaming time to 15 min, and naturally cooling the semi-finished product after foaming for 50 h to obtain a foamed sheet;

[0063] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0064] The preparation method of the functional additive and the wear-resistant modified component is the same as that in Example 1.

[0065] Comparative Example 1

[0066] Preparation of insole composite materials

[0067] (1) The temperature of the internal mixer was raised to 105° C., 50 g of EVA and 25 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 115° C., 10 g of talc, 5.5 g of functional additives and 0.7 g of stearic acid were added. When the temperature was raised to 125° C., 0.5 g of diisopropylbenzene peroxide and 2.5 g of azodicarbonamide were added, and the mixture was mixed for 5 min to obtain a mixed material.

[0068] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 85° C. and the roller gap to 4 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 70° C. and the sheet thickness is 5 mm, thereby obtaining the material after the mixing;

[0069] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 165° C., the foaming pressure to 12 MPa, the foaming time to 12 min, and naturally cooling the semi-finished product after foaming for 45 h to obtain a foamed sheet;

[0070] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0071] The preparation method of the functional additive is the same as that in Example 1.

[0072] Comparative Example 2

[0073] Preparation of insole composite materials

[0074] (1) The temperature of the internal mixer was raised to 105° C., 50 g of EVA and 25 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 115° C., 10 g of talc, 6 g of wear-resistant modification component and 0.7 g of stearic acid were added. When the temperature was raised to 125° C., 0.5 g of diisopropylbenzene peroxide and 2.5 g of azodicarbonamide were added, and the mixture was mixed for 5 min to obtain a mixed material.

[0075] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 85° C. and the roller gap to 4 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 70° C. and the sheet thickness is 5 mm, thereby obtaining the material after the mixing;

[0076] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 165° C., the foaming pressure to 12 MPa, the foaming time to 12 min, and naturally cooling the semi-finished product after foaming for 45 h to obtain a foamed sheet;

[0077] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0078] The preparation method of the wear-resistant modified component is the same as that in Example 1.

[0079] Comparative Example 3

[0080] Preparation of insole composite materials

[0081] (1) The temperature of the internal mixer was raised to 105° C., 50 g of EVA and 25 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 115° C., 10 g of talc, 4.5 g of coffee grounds, 1 g of L-arginine, 6 g of wear-resistant modification component and 0.7 g of stearic acid were added. When the temperature was raised to 125° C., 0.5 g of diisopropylbenzene peroxide and 2.5 g of azodicarbonamide were added, and the mixture was mixed for 5 min to obtain a mixed material.

[0082] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 85° C. and the roller gap to 4 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 70° C. and the sheet thickness is 5 mm, thereby obtaining the material after the mixing;

[0083] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 165° C., the foaming pressure to 12 MPa, the foaming time to 12 min, and naturally cooling the semi-finished product after foaming for 45 h to obtain a foamed sheet;

[0084] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0085] The preparation method of the wear-resistant modified component is the same as that in Example 1.

[0086] Comparative Example 4

[0087] Preparation of insole composite materials

[0088] (1) The temperature of the internal mixer was raised to 105° C., 50 g of EVA and 25 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 115° C., 10 g of talc, 5.5 g of functional additives, 6 g of mullite fiber and 0.7 g of stearic acid were added. When the temperature was raised to 125° C., 0.5 g of diisopropylbenzene peroxide and 2.5 g of azodicarbonamide were added, and the mixture was mixed for 5 min to obtain a mixed material.

[0089] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 85° C. and the roller gap to 4 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 70° C. and the sheet thickness is 5 mm, thereby obtaining the material after the mixing;

[0090] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 165° C., the foaming pressure to 12 MPa, the foaming time to 12 min, and naturally cooling the semi-finished product after foaming for 45 h to obtain a foamed sheet;

[0091] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0092] The preparation method of the functional additive is the same as that in Example 1.

[0093] Comparative Example 5

[0094] Preparation of insole composite materials

[0095] (1) The temperature of the internal mixer was raised to 105° C., 50 g of EVA and 25 g of POE elastomer were added, and the internal mixer was turned on for internal mixing. When the temperature was raised to 115° C., 10 g of talc and 0.7 g of stearic acid were added. When the temperature was raised to 125° C., 0.5 g of diisopropylbenzene peroxide and 2.5 g of azodicarbonamide were added, and the mixture was mixed for 5 min to obtain a mixed material.

[0096] (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 85° C. and the roller gap to 4 mm. After the mixed material is evenly mixed, the temperature of the final sheet is controlled at 70° C. and the sheet thickness is 5 mm, thereby obtaining the material after the mixing;

[0097] (3) placing the material after the open mixing in a foaming mold for foaming treatment, setting the foaming temperature to 165° C., the foaming pressure to 12 MPa, the foaming time to 12 min, and naturally cooling the semi-finished product after foaming for 45 h to obtain a foamed sheet;

[0098] (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

[0099] Performance Testing

[0100] The insole composite materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 5 were made into test samples that met the specifications. The antibacterial rate of the test samples was tested according to GB / T 31402-2023 "Determination of antibacterial activity on the surface of plastics and other non-porous materials", and the test strain was Staphylococcus aureus; the wear resistance of the test samples was tested according to GB / T 5478-2008 "Plastic rolling wear test method"; the test samples were placed in a sealed box, and then 60ppm of isovaleric acid was introduced into the sealed box, and then the box was left standing for 10 minutes. The TVOC detection instrument detected the residual gas concentration in each flask after a specified time from the time of standing, and the deodorization rate after the specified time was calculated. The specific test results are shown in Table 1:

[0101] Table 1 - Performance Test

[0102] Antibacterial rate (%) Wear rate (%) 60min deodorization rate (%) Example 1 99.1 0.15 95 Example 2 99.5 0.10 99 Example 3 99.3 0.13 97 Comparative Example 1 99.0 1.81 94 Comparative Example 2 62.7 0.18 64 Comparative Example 3 89.5 0.16 85 Comparative Example 4 99.0 0.56 94 Comparative Example 5 59.2 1.94 61

[0103] From the test results in Table 1, it can be seen that the samples prepared in Examples 1 to 3 have good antibacterial and deodorizing properties and wear resistance; no wear-resistant modifying component was added to the sample prepared in Comparative Example 1, and compared with the example, the wear resistance of the sample was poor; no functional additives were added to the sample prepared in Comparative Example 2, and the antibacterial and deodorizing properties of the sample were not as good as those of the example; coffee grounds and L-arginine were used to replace the functional additives in the sample prepared in Comparative Example 3, and compared with the example, the antibacterial and deodorizing properties of the sample decreased; mullite fibers were used to replace the wear-resistant modifying components in the sample prepared in Comparative Example 4, and the mullite fibers may not have been organically modified, and agglomeration occurred in the matrix, resulting in a decrease in the wear resistance of the sample; no functional additives and wear-resistant modifying components were added to the sample prepared in Comparative Example 5, so the performance of the sample was poor.

[0104] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A composite material for insoles with antibacterial and deodorizing functions, characterized in that: The invention comprises the following raw materials in parts by weight: 40 to 60 parts of EVA, 20 to 30 parts of POE elastomer, 5 to 15 parts of talc powder, 4 to 6 parts of functional additives, 3 to 7 parts of wear-resistant modification components, 0.5 to 0.9 parts of stearic acid, 0.4 to 0.6 parts of cross-linking agent and 2 to 3 parts of foaming agent.

2. The insole composite material with antibacterial and deodorizing functions according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: S1: drying the coffee grounds at 70-90°C for 4-8h, placing them in a glass fiber sleeve, and then placing them in an extraction tube, adding a solvent in a flask, and controlling the temperature at 80-90°C, performing 4-6 reflux operations, each reflux time being 8-12min, and then drying the deoiled coffee grounds to obtain pretreated coffee grounds; S2: under nitrogen protection, the pretreated coffee grounds are added to N,N-dimethylformamide, ultrasonically dispersed for 20 to 30 minutes, and then isocyanoethyl methacrylate and tin catalyst are added. After the addition is completed, the temperature is raised to 70 to 80°C, and the mixture is stirred for 5 to 7 hours at this temperature, and then allowed to stand for precipitation. The solid material is collected, washed, and vacuum dried to obtain the modified coffee grounds; S3: Mix the modified coffee grounds with deionized water, pour into a reactor, start stirring until a uniform dispersion is formed, add L-arginine, stir at a temperature of 25 to 30° C. for 6 to 8 hours, separate the product, and obtain the functional additive.

3. The insole composite material with antibacterial and deodorizing functions according to claim 2, characterized in that: In step S1, the solvent is n-hexane, and in step S2, the tin catalyst is any one of dibutyltin didodecylsulfide, stannous octoate or dibutyltin dilaurate.

4. The insole composite material with antibacterial and deodorizing functions according to claim 2, characterized in that: In step S3, the mass ratio of the modified coffee grounds to L-arginine is 1:0.1-0.

3.

5. The insole composite material with antibacterial and deodorizing functions according to claim 1, characterized in that: The preparation method of the wear-resistant modified component comprises the following steps: SS1: Mullite fiber is mixed with deionized water, ultrasonically treated for 30 to 50 minutes, then dopamine is added, the pH value of the system is adjusted with Tris-HCL buffer, stirred at room temperature for 12 to 36 hours, allowed to stand and precipitate, solid materials are collected, washed, and vacuum dried to obtain modified mullite fiber; SS2: Ultrasonic disperse 4g of modified mullite fiber in deionized water, add 3g of aluminum nitrate, stir at room temperature for 35-45min, then add ammonia water, stir for 30-50min, filter, wash and dry to obtain the wear-resistant modified component.

6. The insole composite material with antibacterial and deodorizing functions according to claim 5, characterized in that: In step SS1, the pH value of the system is 8-9.

7. The insole composite material with antibacterial and deodorizing functions according to claim 5, characterized in that: In step SS2, the mass fraction of the ammonia water is 10% to 60%.

8. The insole composite material with antibacterial and deodorizing functions according to claim 1, characterized in that: The preparation method of the insole composite material comprises the following steps: (1) raising the temperature of the internal mixer to 100-110° C., adding EVA and POE elastomers, and opening the internal mixer for internal mixing. When the temperature rises to 110-120° C., adding talcum powder, functional additives, wear-resistant modification components and stearic acid. When the temperature rises to 120-130° C., adding a crosslinking agent and a foaming agent, mixing for 3-6 minutes, and obtaining a mixed material. (2) putting the mixed material obtained in step (1) into an open mill for mixing, setting the roller temperature of the open mill to 80-90° C., the roller gap to 2-6 mm, and controlling the temperature of the final sheet after the mixed material is uniform to 40-70° C., and the sheet thickness to 4-7 mm, to obtain the material after the mixing; (3) placing the material after the open mixing in a foaming mold for foaming, and naturally cooling the semi-finished product after foaming for 40 to 50 hours to obtain a foamed sheet; (4) Slicing and cutting the obtained foamed sheet to obtain a shoe insole composite material.

9. The insole composite material with antibacterial and deodorizing functions according to claim 8, characterized in that: In step (1), the cross-linking agent is any one of 1,4-di-tert-butyl peroxide isopropylbenzene or diisopropylbenzene peroxide; the foaming agent is any one of azodicarbonamide, sodium bicarbonate, ammonium bicarbonate or expandable microspheres.

10. The insole composite material with antibacterial and deodorizing functions according to claim 8, characterized in that: In step (3), during the foaming treatment, the foaming temperature is set to 160-170° C., the foaming pressure is set to 10-15 MPa, and the foaming time is set to 10-15 min.

Citation Information

Patent Citations

  • An EVA antibacterial insole and its preparation method

    CN116218071B

  • Antiskid anti-abrasion EVA shoe sole material and preparation method thereof

    CN105175878A

  • Flame-retardant EVA (Ethylene Vinyl Acetate) foaming sole material and preparation method thereof

    CN105199213A

  • EVA antibacterial insole and preparation method thereof

    CN116218071A

  • Formula and process of environment-friendly, soft, deodorant and durable shoes

    CN117402449A